2021
DOI: 10.21037/atm-20-6910
|View full text |Cite
|
Sign up to set email alerts
|

The genomic characteristics of different progression patterns in advanced non-small cell lung cancer patients treated with immune checkpoint inhibitors

Abstract: Background: Fast progression (FP), hyperprogressive disease (HPD), and early death (ED) are the newly reported cancer progression patterns in response to immune checkpoint inhibitor (ICI) treatment. This study aimed to investigate the clinical and genomic characteristics of FP, HPD, and ED following the ICI treatment of advanced non-small cell lung cancer (NSCLC).Methods: We retrospectively reviewed 117 patients with advanced NSCLC who were treated with ICIs from March 2017 to October 2019. FP was defined as (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition to exploring biomarkers from TME, studies also found that MDM2 and ILC3 gene mutations may be risk factors for HPD (16)(17)(18)(19). Li et al (20) found that HPD patients showed more frequent RAD54L mutations than non-HPD patients. Other research has also found that advanced age and past field radiotherapy could also be predictors of HPD (7,15), in addition to an elevated absolute serum neutrophil count (ANC) and C-reactive protein (CRP) (21).…”
Section: Nomogram Establishmentmentioning
confidence: 99%
“…In addition to exploring biomarkers from TME, studies also found that MDM2 and ILC3 gene mutations may be risk factors for HPD (16)(17)(18)(19). Li et al (20) found that HPD patients showed more frequent RAD54L mutations than non-HPD patients. Other research has also found that advanced age and past field radiotherapy could also be predictors of HPD (7,15), in addition to an elevated absolute serum neutrophil count (ANC) and C-reactive protein (CRP) (21).…”
Section: Nomogram Establishmentmentioning
confidence: 99%
“…Besides TGR and TGK, TTF shorter than 2 months is considered an alternative assessment method for HPD. Other indices, such as tumor size, PD at first evaluation (4), fast progression (5), or even early death, were used (6). There is still no consensus on how to evaluate this phenomenon.…”
Section: Introductionmentioning
confidence: 99%